CONCEALED CHARACTER VALUES ON LECTURERS’ VERBAL FEEDBACK IN ENGLISH TEACHING - Adetya Norizkyka; Yulieda Hermaniar (Universitas Ahmad Dahlan)
Integrating values in the teaching and learning of English becomes the main concern of education in Indonesia. There are 18 values of character building in national character and cultural education which are demanded to be integrated in the teaching and learning process. However, the implementation is mostly heard from lower level of education. Therefore, it is considered important to conduct the study on the higher level of education or university, especially in the productive course such as speaking class. This leads to the interest on conducting study on the lecturers’ verbal feedback in English teaching as the reflection of teaching character values. Preliminary study was conducted by interviewing students of speaking class to get information related to the technique, method, and material used in the speaking class. Three speaking class’ lecturers will be the subject of the research. Observation is conducted to collect the data by using observation sheet and recorder as instrument. The interview takes students as the object in order to get their perspective to the feedback give. The result shows that there are three kinds of verbal feedback used. They are corrective feedback, interactive feedback, and evaluative feedback. The result of interview shows students positive perspective toward the feedback and the values they acquired from the feedback give. From the observation and interview, it can be concluded that the concealed values taught during the speaking class, they are disciplines, curious, respect, democracy, and communicative.